On the uncertainty of the legal regime of non-cash money under the legislation of the Republic of Kazakhstan as a reason for the violation of the rights and legitimate interests of the owners of non-cash money in case of bankruptcy of banks - Proskurina, K.Yu. (Bulletin of the Karaganda University “Law Series”, 2022)
This study provides a legal analysis of the legal literature and the current civil legislation of the Republic of Kazakhstan, the legislation on banks and banking, rehabilitation and bankruptcy to identify legal norms that lead to a violation of the rights and legitimate interests of owners of non-cash money held in bank accounts in a bankrupt bank. In practice, bank customers are often included in the number of creditors of a bankrupt bank due to the uncertainty of the legal regime of non-cash money in the current legislation of the Republic of Kazakhstan. This study is intended to analyze what legal norms contribute to the violation of the rights of bank customers, how and to what extent the choice of the appropriate concept of non-cash money will eliminate such violations and increase the degree of protection of the rights and legitimate interests of citizens and organizations in their legal relations with banks. For the purposes of this study, the three most common concepts of non-cash money in legal science were chosen: non-cash money as obligations of the central bank, non-cash money as rights of claim against a second-tier bank, and non-cash money as incorporeal things. The methodological basis of this study was the method of legal analysis, the method of hermeneutics, and the formal-logical method. The author of this article, based on the results of the legal analysis, proposes the author’s concept of non-cash money and practice-oriented recommendations for making changes and additions to the current legislation of the Republic of Kazakhstan.